2021
DOI: 10.1002/pen.25763
|View full text |Cite
|
Sign up to set email alerts
|

Polymer melt rheology: Advantages of frequency sweeps using randomly selected frequencies*

Abstract: Measurement of the viscoelastic properties of polymer solids, melts, and solutions is broadly practiced. The so‐called “frequency sweep” appears in thousands of publications, with data covering up to five decades of frequency to reveal, for example, the relative molecular size of a polymer. To perform these experiments, the frequency range is typically “swept” from high to low frequency or vice versa. Unfortunately, this confounds frequency with run time. This is more than annoying; time effects can result in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The work done by Montgomery T. Shaw showed that, for samples with time dependent change, random ordering of the frequencies tested result in time becoming a random error and decouples the affects due to the angular frequency applied from the time change of the sample. [ 30 ] To determine if there was a time dependent change in the PE‐GMA‐V vitrimer samples, the results from the random frequency tests were compared to the traditional frequency test and are shown in Figure 8A. For all PE‐GMA‐V vitrimers, the storage modulus from the random frequency of the samples deviates from the storage modulus as a result of the traditional frequency tests, indicating that some ongoing change occurs during testing.…”
Section: Resultsmentioning
confidence: 99%
“…The work done by Montgomery T. Shaw showed that, for samples with time dependent change, random ordering of the frequencies tested result in time becoming a random error and decouples the affects due to the angular frequency applied from the time change of the sample. [ 30 ] To determine if there was a time dependent change in the PE‐GMA‐V vitrimer samples, the results from the random frequency tests were compared to the traditional frequency test and are shown in Figure 8A. For all PE‐GMA‐V vitrimers, the storage modulus from the random frequency of the samples deviates from the storage modulus as a result of the traditional frequency tests, indicating that some ongoing change occurs during testing.…”
Section: Resultsmentioning
confidence: 99%